KIRGIZ TÜRKÇESİ'NDE ÜNSÜZLER VE ÜNSÜZ OLAYLARI - ÖZEREN, MEHMET (Fırat Üniveristesi, 2008)
Kırgız Türkçesinde Ünsüzler ve Ünsüz Olayları adlı çalışma; giriş, ünlü ve ünsüzler, ünsüz özellikleri, ünsüz olayları olmak üzere dört kısımdan oluşmaktadır. Giriş bölümünde Kırgız adı, Kırgız Türklerinin tarihi, edebiyatı ve Kırgız Türkçesi hakkında bilgi verilmiştir. Birinci bölümde ses, ünlü, ünsüz, ünlü-ünsüz farkı ve ünsüzlerin sınıflandırılması üzerinde durulmuştur. İkinci bölümde Kırgız Türkçesindeki ünsüzlerin tanımlanması yapılmıştır. Daha sonra her ünsüzün Türkçe sözcüklerdeki görünümü ve özellikleri, alıntı sözcüklerdeki görünümü ve özellikleri sözcüğün başında, ortasında, sonunda ayrı ayrı incelenmiştir. Üçüncü bölümde ise Türkçe ve alıntı sözcüklerde başta, ortada ve sonda tespit edilen ünsüz olayları üzerinde durulmuştur.

The study and fuction of consonants in Khirgiz Turkish consists of four sections; an introduction, vowels and consonants, consonants and their characteristics and finally consonant funtions. In the introduction section some information is given concerning the name Khirgiz, the literature and history of bath Khirgiz Turks and the Khirgiz Turkish language. In the first section the sound, the vowels and consonants, the difference between the vowels and consonants, and classification of consonants are examined. In the second section there is a definition of Khirgiz Turkish. The appearance and characteristics of each consonant in Turkish words, and their appearance and characteristics in the begining, in the mid and at the end of borrowed words are examined in details. In the third section the function of consonants which take place in the begining, in the mid and at the end of both Turkish words and borrowed words are examined.
The study and fuction of consonants in Khirgiz Turkish
Keywords: Türk Dili ve Edebiyatı